PENDAMPINGAN PENERAPAN ALAT PEMANGGANG LEMANG PADA INDUSTRI RUMAH TANGGA (IRT) LEMANG CIK OKOT DESA RAMBAH TENGAH BARAT - Junaidi, Nurhikmah Sasna; Kusmiati, Kusmiati; Mela, Fefti Yulian; Genesa Hatika, Rindi; Lestari, Bunga; Nuraini, Nuraini (Mejuajua: Jurnal Pengabdian pada Masyarakat, 2025)
The Community Service Program aims to implement a lemang roasting tool at IRT Lemang Cik Okot. Assistance is provided to make it easier to cook lemang in a shorter time before using the roasting tool. This is done to reduce the risk of burns or direct exposure to lemang roasting smoke during the cooking process. Traditionally, the lemang baking process has been relatively long and requires flipping the lemang every 15 minutes by hand to ensure even cooking. This assistance is provided to speed up the lemang baking process and reduce the risk of burns or hot hands when flipping the lemang. The results of this assistance show that the lemang baking tool is effective for baking lemang and speeds up the cooking process.